2011
DOI: 10.1007/s10616-010-9327-4
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta 1 in adipose derived stem cells conditioned medium is a dominant paracrine mediator determines hyaluronic acid and collagen expression profile

Abstract: Conditioned medium from adipose derived stem cells (ADSC-CM) stimulates both collagen synthesis and migration of fibroblasts, and accelerates wound healing in vivo. Recently, the production and secretion of growth factors has been identified as an essential function of adipose-derived stem cells (ADSCs). However, the main soluble factor of ADSC-CM which mediates paracrine effects and its underlying mechanism has not been elucidated yet. In this study, we considered transforming growth factor-beta1 (TGF-β1) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 28 publications
2
44
1
Order By: Relevance
“…This hypothesis is supported by previous studies which revealed that several cytokines relevant to osteogenesis such as hepatocyte growth factor, vascular endothelial growth factor (VEGF), insulin-like growth factor-1, and transforming growth factor b were expressed by human ADSCs. [50][51][52] Moreover, it has been shown that ADSCs are also able to promote angiogenesis by secreting a number of pro-angiogenic factors including angiopoietin-1, stromal derived factor-1, and VEGF (reviewed in ref 53 ). These angiogenic factors may also play roles in the anabolic effect of ADSCs by recruiting host endothelial progenitor cells and stimulating neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by previous studies which revealed that several cytokines relevant to osteogenesis such as hepatocyte growth factor, vascular endothelial growth factor (VEGF), insulin-like growth factor-1, and transforming growth factor b were expressed by human ADSCs. [50][51][52] Moreover, it has been shown that ADSCs are also able to promote angiogenesis by secreting a number of pro-angiogenic factors including angiopoietin-1, stromal derived factor-1, and VEGF (reviewed in ref 53 ). These angiogenic factors may also play roles in the anabolic effect of ADSCs by recruiting host endothelial progenitor cells and stimulating neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…What paracrine factors are involved in these studies of epidermal/dermal formation remain unknown but possible paracrine factors may include HGF, VEGF, TGF 1, TGF 3, G-CSF, GM-CSF, IL6, and IL8 [292]. In support of this, Jung and colleagues have reported that conditioned medium from ASCs can increase CNI, CNIII, and hyaluronic acid synthesis by human dermal fibroblasts and that neutralizing antibodies to TGF 1 can abolish this effect [296].…”
Section: In Vivo Ectoderm Regeneration-epithelial and Epidermalmentioning
confidence: 99%
“…Proposed mechanisms include the secretion of TGF-β1 by ADSCs, which provides significant inhibition of the melanin synthesis through a downregulation of tyrosinase and expression of tyrosinase-related protein 1 (TRP1). In addition, TGF-β1 is a well-known dominant paracrine mediator, which determines the hyaluronic acid and collagen expression profiles [44]. Another group recently confirmed this effect and proposed that inhibition of melanin synthesis can be realized via interleukin-6 [45].…”
Section: Mosaic Skin Structure - Is There a Link To Dwat Clusters Thamentioning
confidence: 99%